âTAONG VLAMINGâ PEMERINTAHAN DE VLAMING, PERLAWANAN RAKYAT DAN PENGARUHNYA DI SAPARUA TAHUN 1647-1656 - , Johan Pattiasina,Spd, Dr. Sri Margana, M.Phil ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Studies on Maluku during the period of VOC have been done, but they focused more on the island of Ambon, Ternate and Banda. Meanwhile the Saparua Island as the area which also suffered from the VOCâs policies was lack of attention. This study discusses about the changes that occurred in Saparua Island in the reign of De Vlaming during the period 1647-1655. The main subject of this study is the changing pattern of settlement and ethnic composition on Saparua Island. The sources used in this study are the VOC published documents, and oral tradition that developed in Saparua society. In this study, the author found that, the changes that occurred in Saparua during the period 1647-1656 were the result of the VOCâs policies that aimed to control the territory and trade of spice in Maluku. The changes reached its climax when De Vlaming conquered the Iha and deported their citizen. That condition was affecting to the formation of new settlement on the coast of Northern Saparua, shifted in traditional governance leadership, citizen segregation, and Ambon, Saparua, Haruku and Nusalaut Island were become central production of clove for VOC. The conclusion of this study is that the changes occurred on Saparua in period of De Vlaming was the consequence of some policies that applied by the VOC in controlling the territory and trade of spice. These policies resulted in the changes in formation of ethnic, social and religious in Saparua.